RADICALIZING INDONESIAN MODERATE ISLAM FROM WITHIN: The NU-FPI Relationship in Bangkalan, Madura (JOURNAL OF INDONESIAN ISLAM, 2013)
This article tries to present the most current phenomenon of how moderate Islam can live side by side with radical Islam. By focusing its analysis on the dynamics of political life in Bangkalan, Madura, the paper argues that the encounter between these two different ideological streams is possible under particular circumstances. First, there is a specific political situation where the moderate Islam is able to control the political posts. Second, there is a forum where they can articulate Islamic ideas in terms of classical and modern political movements. This study has also found out that the binary perspective applied in the analysis of Islamic movement is not always relevant. The fact, as in the case of Bangkalan, is far more complex, in which NU and Islamic Defender Front (FPI) can merge. This is so because at the beginning, FPI’s management in the city is led by kyais or/and prominent local NU leaders.